Modern Muslim states between Islamic law and international human rights law - Baderin, Mashood A. (2001)
This thesis examines the important question of whether or not Islamic law and international human rights are compatible and whether Muslim States can comply with international human rights law while they still adhere to Islamic law. The traditional arguments on the subject are examined and responded to from both international human rights and Islamic legal perspectives. The thesis formulates a synthesis between two extremes and argues that although there are some differences of scope and application, that does not create a general state of dissonance between Islamic law and international human rights law. It is argued that the differences would be easier to address if the concept of human rights were positively established from within the themes of Islamic law rather than imposing it as a concept alien to Islamic law. To avoid a simplistic generalisation of the arguments, each Article of the international bill of rights (ICCPR and ICESCR) and some relevant articles of the Convention on the Elimination of all Forms of Discrimination against Women are analysed in the light of Islamic law. The thesis theoretically engages international human rights law in dialogue with Islamic law and then evaluates the human rights policy of modern Muslim States within the scope of that dialogue. The State Practice of six Muslim States is examined as case studies to establish the arguments of the thesis. The thesis concludes, inter alia, that it is possible to harmonise the differences between Islamic law and international human rights law through the adoption of the margin of appreciation doctrine by international human rights treaty bodies and the utilisation of the Islamic law doctrines of maqâsid al-sharî‘ah (overall objective of Sharî‘ah) and maslahah (welfare) by Muslim States in their interpretation and application of Islamic law respectively. It is asserted that Islamic law can serve as an important vehicle for the enforcement of international human rights law in the Muslim world and recommendations are advanced to that effect in the conclusion.